The historical roots of corruption: mass education, economic inequality, and state capacity - Uslaner, Eric M. (Cambridge University Press, 2017)
Machine generated contents note: 1. The theoretical framework; 2. The quantitative evidence; 3. Education in the developed countries (Northern and Southern Europe); 4. Education outside the developed countries: Africa, Latin America, Asia; 5. Education in the Anglo-American countries; 6. Is path dependence forever: how some countries reduced corruption